2021
DOI: 10.3390/ijerph182211936
|View full text |Cite
|
Sign up to set email alerts
|

Affordances for Motor Development in the Home Environment for Young Children with and without CHARGE Syndrome

Abstract: Affordances in the home environment are critical to early motor development. Currently, the home environment has not been examined in children with deafblindness or severe disabilities. The present study examined differences in, and relationships between, the home environment and motor development in children with and without CHARGE syndrome. CHARGE syndrome is a low-incidence, complex disorder with sensory and motor impairments. Participants included 28 parents of children with CHARGE syndrome and 32 parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…This most fundamental developmental characteristic was described as "stability in body posture" (Preisler and Preisler, 2005;Beach et al, 2021), "bodily expressions" (Preisler and Preisler, 2005), and "motor development" (Narayan and Bruce, 2006;Beach et al, 2021). Preisler and Preisler (2005) described this characteristic in six children with CDB.…”
Section: Developing and Exploring One's Own Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…This most fundamental developmental characteristic was described as "stability in body posture" (Preisler and Preisler, 2005;Beach et al, 2021), "bodily expressions" (Preisler and Preisler, 2005), and "motor development" (Narayan and Bruce, 2006;Beach et al, 2021). Preisler and Preisler (2005) described this characteristic in six children with CDB.…”
Section: Developing and Exploring One's Own Bodymentioning
confidence: 99%
“…A study by Beach et al (2021) compared the outcomes of a parental self-report questionnaire about their child's motor development in the home environment. Twenty-eight parents of a child with CDB and 32 parents of a child without disabilities completed this questionnaire (all children aged 1-3 years).…”
Section: Developing and Exploring One's Own Bodymentioning
confidence: 99%
“…With these tools, several studies have reported a signi cant association between the level of affordances in the home and the child's motor skill development. In other words, higher home affordance scores are related to higher motor skill levels (Beach et al, 2021;Cao et al, 2021;Mori et al, 2013;Saccani et al, 2013;Valadi & Gabbard, 2020).…”
Section: Introductionmentioning
confidence: 99%